2011
DOI: 10.1556/jfchem.2011.00013
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Synthesis-Purification System to Accelerate the Generation of Compounds in Pharmaceutical Discovery

Abstract: We report herein a high-throughput integrated synthesis-purification platform termed SWIFT (synthesis with integrated-flow technology) and processes that accelerate the rate at which validated small-molecule organic compounds are generated. A segmented-flow synthesizer was integrated to a preparative HPLC-MS, where each reaction product was purified immediately upon reaction completion. Further, automated structure-validation processes accelerate the rate at which drug discovery candidates are available for bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 22 publications
0
23
0
2
Order By: Relevance
“…Using both CATS2 [9] pharmacophores and Morgan substructure fingerprints, [10] the machine-learning algorithm generated 5774 candidate amines, from which we selected 1-4 for synthesis and biochemical profiling [ Table 1, Figure 1 A, Supporting Information (SI)], based on the predicted 5-HT 2B selectivity over 5-HT 2A/C . [11] We used an automated Cetoni neMESYS microfluidic system equipped with low-pressure, pulsation-free syringe pumps. [11] We used an automated Cetoni neMESYS microfluidic system equipped with low-pressure, pulsation-free syringe pumps.…”
mentioning
confidence: 99%
“…Using both CATS2 [9] pharmacophores and Morgan substructure fingerprints, [10] the machine-learning algorithm generated 5774 candidate amines, from which we selected 1-4 for synthesis and biochemical profiling [ Table 1, Figure 1 A, Supporting Information (SI)], based on the predicted 5-HT 2B selectivity over 5-HT 2A/C . [11] We used an automated Cetoni neMESYS microfluidic system equipped with low-pressure, pulsation-free syringe pumps. [11] We used an automated Cetoni neMESYS microfluidic system equipped with low-pressure, pulsation-free syringe pumps.…”
mentioning
confidence: 99%
“…The efficiency of catalytic oxidation of methanol was examined in a segmented flow system with zones of different catalysts in a perfluorinated carrier, where, under high pressure, the mixture of substrate and oxygen was introduced through the Teflon membrane [142]. It can be concluded that the commercial success of clinical analyzers with segmented flow between 1960 and 1980 found a kind of continuation/replication in the process of designing segmented flow synthesizers to accelerate the generation of compounds in pharmaceutical discovery [143].…”
Section: Detectors Reactors Manifoldsmentioning
confidence: 99%
“…Researchers at Abbott have created a synthesis and purification platform in flow for some of the most commonly used reactions in the pharmaceutical chemistry, for example, formation of amides, triazoles, and ureas as well as reductive amination, nucleophilic substitution, and sulfonylation. Reactions were performed in 10 min with a flow rate of 146 μL min −1 , which resulted in a throughput of 48‐member libraries in less than five days 40. Access to druglike thiazoles and pyrazoles with a mesoscale flow reactor has also been reported 41.…”
Section: Application To Bioactive Chemical Agentsmentioning
confidence: 99%